Synorthocladius Thienemann from China, with a review of the genus (Diptera: Chironomidae: Orthocladiinae) - Liu, Yuedan; Wang, Xinhua H. (Zootaxa, 2005)
The orthoclad genus Synorthocladius is reviewed. Synorthocladius bifidus is described and figured based on males from China. Synorthocladius semivirens (Kieffer) is redescribed and illustrated based on Chinese specimens. Synorthocladius conicus (Freeman) is transferred to the genus Bryophaenocladius. A key to males of Synorthocladius of the world is presented, and the generic diagnosis is emended.